Folding techniques for designers : from sheet to form - Jackson, Paul, 1956- (London : Laurence King Pub., 2011)
This unique, practical handbook explains the key techniques of folding, such as pleated surfaces, curved folding, and crumpling. It covers more than 70 techniques explained by clear step-by-step drawings, crease pattern drawings, and specially commissioned photography.
Introduction -- Dividing the paper -- Symmetrical repeats -- Stretch and skew -- Polygons -- Accordion pleats -- Knife pleats -- Box pleats -- Incremental pleats -- Spiral pleats -- Gathered pleats -- Twisted pleats -- Basic V-pleats -- Making by hand -- Variations -- Multiple Vs -- Grid Vs -- Cylindrical Vs -- Complete surfaces -- X-form spans -- V-fold spans -- Parabolas -- Boxes -- Bowl forms -- No crease -- One crease -- The basic technique -- Linear crumpling -- Rotational crumpling -- Advanced concepts.
Accompanying CD-ROM contains diagrams (crease pattern drawings) in PDF format assigned numbers that correspond to those found within the book.
ARC
Keywords: Paper folding (Graphic design) -- Handbooks, manuals, etc; Paper work -- Handbooks, manuals, etc